2012
DOI: 10.1111/j.1467-9612.2011.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Linear Asymmetries and the LCA

Abstract: Abstract.  Kayne (1994) was instrumental in putting linear asymmetries on the generative research agenda. His Linear Correspondence Axiom is seen as a restrictive, conceptually attractive proposal supported by a wealth of empirical evidence. In this paper, we take issue with this assessment. (i) We show that for every structure that violates the LCA, there is an LCA‐compatible counterpart, including rightward movement structures and structures with rightward specifiers. (ii) We discuss Cinque's (2005) LCA‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
120
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 66 publications
3
120
0
Order By: Relevance
“…This sequence corresponds to the order found when modifiers of the lexical head are to its left. This proposal is central to the theory, and it is shared among the various alternatives to Cinque's account (see Steddy & SamekLodovici 2011, Abels & Neeleman 2012, Medeiros 2012.…”
Section: Left-right Asymmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…This sequence corresponds to the order found when modifiers of the lexical head are to its left. This proposal is central to the theory, and it is shared among the various alternatives to Cinque's account (see Steddy & SamekLodovici 2011, Abels & Neeleman 2012, Medeiros 2012.…”
Section: Left-right Asymmetrymentioning
confidence: 99%
“…Abels & Neeleman (2012) argue that this order should rather be derived by allowing for a different linearization of the underlying structure, with the heads to the right, as shown in (38b). What is, however, important is that all the approaches mentioned above use phrasal movement to derive the so-called mirror-violating orders in the post-head position.…”
Section: Left-right Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Although in his account of Universal 20 and its exceptions Cinque (2005) adopts Kayne's (1994) Linear Correspondence Axiom, which necessitates specific assumptions about the X-bar theoretic status and syntax of what are assumed to be functional heads and phrasal modifiers, Abels and Neeleman (2012b) have shown that the account follows already from the following substantially weaker assumptions: (i) The underlying hierarchical arrangement of demonstrative, numeral, descriptive adjective, and noun within the extended projection of the noun is fixed in such a way that the demonstrative c-commands the remaining three elements, the numeral c-commands the adjective and the noun, and the adjective c-commands the noun. (ii) Phrase structure obeys the non-tangling condition.…”
Section: The Fundamental Left-right Asymmetrymentioning
confidence: 99%
“…This paper discusses the concepts needed to generalize Cinque's theory and situates word order variation in the Germanic verb cluster in the context of a Cinque-style general theory of neutral word order. Abels and Neeleman (2012b) shows that, although Cinque's theory is formulated assuming Kayne's (1994) Linear Correspondence Axiom and a cartographic perspective on structures, it effectively relies on the following assumptions: the hierarchy of nominal modifiers is universally fixed; phrase structure obeys the non-tangling condition, which disallows discontinuous constituents (see Ojeda 2006 for discussion and references); 2 movements deriving neutral orders within DP end in positions strictly c-commanding their traces, are leftward, and affect only constituents containing the lexical noun. This is a promising blueprint for a general theory of unmarked word order because it allows for a straightforward generalization as follows: Phrase structure obeys the non-tangling condition; movements deriving unmarked word order within the extended projection of a lexical head L end in positions strictly c-commanding the trace, are leftward, and affect only constituents containing L. 3 The specific hierarchical arrangement of elements remains the only parochial assumption within the theory.…”
mentioning
confidence: 99%